Bioprocess intensification for isopropanol, butanol and ethanol (IBE) production by fermentation from sugarcane and sweet sorghum juices through a gas stripping-pervaporation recovery process. (1st December 2020) - Rochón, Eloísa; Cortizo, Gastón; Cabot, María Inés; García Cubero, María Teresa; Coca, Mónica; Ferrari, Mario Daniel; Lareo, Claudia
Abstract: Butanol and isopropanol are important commodity chemicals with a variety of applications. One of the main obstacles for biobutanol production by IBE (isopropanol–butanol–ethanol) fermentation is the intensive energy consumption for product recovery by conventional distillation due to low butanol titer in fermentation broth caused by butanol toxicity to cells. In the present study, butanol production by batch IBE fermentation coupled to an in situ gas stripping-pervaporation process to recover the butanol is proposed using Clostridium beijerinckii DSM 6423 and a mixture of sugarcane-sweet sorghum juices as substrate. Gas stripping was used to continuously remove butanol from the fermentation broth, followed with pervaporation to further concentrate butanol. The strategy used allows alleviating butanol inhibition and to recuperate a condensate containing high butanol concentration (559 g/L). A kinetic model describing butanol production by IBE fermentation was developed. Kinetic parameters and experimental data were used to estimate the energy consumption of the sugarcane-sweet sorghum IBE production process. It was found that although the IBE production process showed less energy consumption (15%) than the butanol production process by ABE (acetone-butanol-ethanol) fermentation, a substantial improvement is still necessary for the process to be energetically/economically attractive.